High incidence of clinical malaria among asymptomatic Plasmodium falciparum infected children receiving SMC with sulfadoxine-pyrimethamine and amodiaquine (SP + AQ) in Koulikoro, Mali - Daouda Sanogo; Mahamoudou Toure; Moussa Keita; Fousseyni Kane; Soumba Keita; Ibrahima Sanogo; Sory Ibrahim Diawara; Cheick Oumar Tangara; Hamady Coulibaly; Bourema Cisse; Sidibé M’Baye Thiam; Mahamadou Diakite; et al. (Malaria Journal)
Abstract Background Seasonal malaria chemoprevention (SMC) with sulfadoxine-pyrimethamine and amodiaquine (SP + AQ) involves the monthly administration of therapeutic doses to children under five years of age during periods of high risk of malaria in regions where malaria transmission is highly seasonal. Current SMC guidelines recommend administering the same treatment to both non-infected and asymptomatic Plasmodium falciparum-infected children. However, a critical knowledge gap remains the impact asymptomatic infection on the efficacy of SMC in preventing clinical malaria over a four-week period. This study aimed to evaluate the risk of clinical malaria and its association with children's infection status during SMC treatment. Methods This study was conducted in the Koulikoro health district of Mali and focused on children under 10 years of age. A total of 726 children in 2019 and 1452 children in 2020 were randomly selected and followed throughout the SMC campaigns. The prevalence of asymptomatic P. falciparum infection was assessed in each round using microscopy prior to SMC drug administration. Children were passively monitored over a four-week period to record the incidence of clinical malaria. Data analysis was performed using R-Studio software. The risk of clinical malaria based on infection status was estimated through logistic regression analysis, and a Kaplan–Meier curve was used to compare survival times between infected and uninfected children. Proportions were compared using the Pearson Chi-square test, with statistical significance set at p < 0.05. Results The average prevalence of asymptomatic P. falciparum infection was 11.0% across study years. Prevalence was notably higher among children aged 5 to 9 years old in 2019 (p < 0.001) and 2020 (p = 0.016). Asymptomatic infected children had a significantly higher risk of clinical malaria during both transmission seasons: 2019: (RR = 3.05, CI [2.04–4.72]) and 2020 (RR = 1.43, CI [1.04–1.97]). Furthermore, the time to the first malaria episode was significantly shorter among infected children in both years (p < 0.001 for 2019, p = 0.01 for 2020). Conclusion These findings demonstrate an elevated risk of clinical malaria in asymptomatic infected children during SMC implementation. Screening and treating P. falciparum infections prior to SMC administration could substantially enhance the effectiveness of this strategy in reducing malaria morbidity in endemic areas.